Eksekusi Hak Tanggungan Akad Musyarakah Mutanaqisah - Sherhan, Sherhan (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
Ideally, Islamic banks analyze aspects of fairness between creditors and debtors when choosing the execution of debtor guarantees. In fact, it was found that the execution of dependent rights in Islamic banks, especially with MMQ (musyarakah mutanaqishah) contracts, was more beneficial to creditors and tended to tyrannize debtors. This study analyzes the theory of justice in the implementation of the execution of dependent rights by Islamic Banks against defaulting financing debtors with MMQ contracts. The goal is that transactions at Sharia Banks are always based on Islamic sharia rules and principles. This research applies qualitative methods with a rationale based on literature studies to analyze legislation, legal provisions and conformity to applicable regulations. The results of the study concluded that injustice occurs when the execution of dependent rights, the proceeds of the sale of the debtor's financing collateral assets default more harm the debtor.